Healthy aging promotion model referenced in Nola Pender's theory - Rosane Barreto Cardoso; Célia Pereira Caldas; Marcos Antônio Gomes Brandão; Priscilla Alfradique de Souza; Rosimere Ferreira Santana (Associação Brasileira de Enfermagem, 2021)
ABSTRACT Objectives: to model the process of promoting healthy aging from the conceptual analysis proposed by Walker and Avant and Nola Pender's Health Promotion Model. Methods: this is a descriptive and theoretical study, with a qualitative approach. Elements resulting from conceptual analysis were used to model a healthy aging promotion process based on Nola Pender's Health Promotion Model. Results: in conceptual analysis, seven antecedents, seven attributes and three consequences of the concept of healthy aging were identified. Final Considerations: the proposed Health Promotion Model represents a structure that in an instrumental way can guide the nursing process application in gerontological clinical practice. This can guide nurses in identifying diagnoses, establishing outcomes and implementing interventions aimed at promoting the elderly's health.